Las huertas urbanas como protagonistas en el cambio sostenible (2022)
The items are presented below. on which relevance is justified of the project, beginning with the choice of the context, followed by the importance of industrial design specifically in biodesign and design to promote the behavior change aligned to Study of existing regulations that allow the project to be relevant.